2017
DOI: 10.3748/wjg.v23.i25.4632
|View full text |Cite
|
Sign up to set email alerts
|

Long-term irritable bowel syndrome symptom control with reintroduction of selected FODMAPs

Abstract: AIMTo investigate the long-term effect of dietary education on a low fermentable oligosaccharide, disaccharide and polyol (FODMAP) diet on irritable bowel syndrome (IBS) symptoms and quality of life (QoL).METHODSParticipants with IBS (Rome III) were randomized to two groups. Group I commenced a low FODMAP diet at baseline. At three months, group II, so far a comparator group, crossed over to a low FODMAP diet while group I started re-challenging foods. All patients completed the IBS SSS (IBS symptom severity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
166
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(181 citation statements)
references
References 68 publications
(87 reference statements)
9
166
3
3
Order By: Relevance
“…With a mean IBS‐QOL score of 72.3 out of a total of 100, the long‐term IBS related QOL appears to be similar to, or even slightly better than, the results found in short‐term studies . The predominant disease course in the participants of the study was mild IBS with indolent course.…”
Section: Discussionsupporting
confidence: 49%
“…With a mean IBS‐QOL score of 72.3 out of a total of 100, the long‐term IBS related QOL appears to be similar to, or even slightly better than, the results found in short‐term studies . The predominant disease course in the participants of the study was mild IBS with indolent course.…”
Section: Discussionsupporting
confidence: 49%
“…Changes to nutrient intake have also been noted following institution of the low FODMAP diet, with reductions in total energy, carbohydrate, fiber and calcium intake reported during the initial restrictive phase . These effects may resolve following re‐challenge, as suggested by data to date from long‐term studies . It may be that the institution of any diet and/or involvement in a dietary study has effects on total energy intake, as total energy intake was also reduced in comparison groups randomized to the NICE guidelines .…”
Section: Safety Issues Related To Dietary Therapies In Irritable Bowementioning
confidence: 98%
“…Long‐term studies: Two recently published papers showing efficacy of the low FODMAP diet in the long‐term following re‐challenge …”
Section: Dietary Therapies For the Treatment Of Irritable Bowel Syndromementioning
confidence: 99%
“…Therefore, it would be expected that a low‐FODMAP diet would reverse this prebiotic effect, but this is not necessarily the case. Several well‐controlled studies assessing varying FODMAP intake have shown that a low‐FODMAP diet has no effects on bacterial diversity, a marker of good gut health, among patients with IBS, Crohn's disease, or healthy subjects . Total bacterial abundance decreases in these patient populations, but the health significance of this is unknown and possibly favorable as indicated in a study in which fecal water from patients on a low‐FODMAP diet increased markers of inflammation when infused into a rat colon .…”
Section: Introductionmentioning
confidence: 99%